The Rhythm Is Gonna Get You: The Influence of Circadian Rhythm Synchrony on Self‐Control Outcomes. Issue 11 (November 2014) - Curtis, Jessica; Burkley, Edward; Burkley, Melissa
Abstract This article aims to bridge the circadian and self‐control literatures by suggesting that people's self‐control performance varies as a function of their circadian preferences (i.e., chronotype). We review evidence for this assertion across a wide range of self‐control domains, including cognitive processing, emotion regulation, interpersonal relationships, and social influence. Across these widely ranging behaviors, the results indicate that when people's circadian preference matches the time of day, a synchrony effect occurs, and self‐control performance is at its peak. Therefore, people are more likely to display self‐regulatory failures and give in to temptations when there is a mismatch between their circadian preferences and time of day. Overall, this article offers new insights into the relationship between circadian preferences and self‐control and suggests novel and exciting new directions for future research.